THE ROLE OF GENERATIVE ARTIFICIAL INTELLIGENCE IN PROGRAMMER TRAINING: OPPORTUNITIES AND CHALLENGES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Artificial intelligence has rapidly entered people's daily lives and has innovated many traditional models by integrating AI technologies. The need for changes in educational practices has come to the forefront. This article outlines various possibilities for using generative artificial intelligence in programming education. Different examples are presented, including code generation, debugging and optimization, documentation and commenting, automated testing, conversion between different programming languages, and more. Additionally, some risks and limitations are discussed.